HEALTH LITERACY AND PHYSICAL FITNESS PROFILE OF STUDENTS AT SENIOR HIGH SCHOOL - Utama, Nur Budhi; Destriani , Destriani; Aryanti, Silvi (Universitas Negeri Padang, 2023)
This research aims to determine the level of health literacy and physical fitness of students at Senior High School PGRI 2 Palembang, This study is a quantitative descriptive research.. There are two methods used in this research, namely the survey method using the Health Literacy Study-European-Short Question 10-Indonesia questionnaire to assess the level of health literacy and the test method using the TKPN to determine the level of physical fitness. In this study, the research population consists of all students at Senior High School PGRI 2 Palembang, totaling 806 students. The sample for this research uses the Slovin formula approach, which results in a sample size of 88 students from classes X1, X2, and X3. Data analysis techniques employ quantitative descriptive analysis presented in the form of percentages using Microsoft Excel. The results of the health literacy level showed that 31.8% of students (28 students) were in the “insufficient” category, 33% (29 students) were in the “problematic” category, 30.7% (27 students) were in the sufficient” category, and 4.5% (4 students) were in the “perfect” category. Based on the average score is 28.8, the health literacy level of students at Senior High School PGRI 2 Palembang falls into the “problematic” category. For physical fitness the data reveals that 15.9% of students (14 students) have a “very good” level of physical fitness, 37.5% of students (33 students) have a “good” level of physical fitness, 46.6% of students (41 students) have “sufficient” level of physical fitness, and 0% of students (0 students) have “low” or “poor” physical fitness. Based on the average score is 3.15, the level of physical fitness of students at Senior High School PGRI 2 Palembang falls into the “good” category.